31‐4: Invited Paper: 3D Eyebox in Augmented and Virtual Reality Optics. Issue 1 (29th May 2019) - Cakmakci, Ozan; Hoffman, David M.; Balram, Nikhil
Abstract : The eyebox volume is a key design parameter in the optical design of augmented and virtual reality optics. The extent of the eyebox volume determines the experience of a user in seeing the entire virtual magnified image. Furthermore, a 3D description of eyebox facilitates the design of augmented and virtual reality products for a population of users. We define 3D eyebox and discuss visualization approaches to communicate it within interdisciplinary product design groups focused on research and development of augmented and virtual reality optics.